PENGARUH SKALA USAHA, PEMBIAYAAN DAN HUBUNGAN KEUANGAN BANK TERHADAP KINERJA UMKM - Naibaho, Zesri Ade Putri; Ompusunggu, Hermaya (LPPM Universitas Putera Batam, 2024)
The purpose of this study is to examine how bank financial relationships, business scale, and financing affect the performance of MSMEs in Bengkong District. A quantitative approach using multiple linear regression analysis approaches is the research methodology employed. The findings demonstrated that the performance of MSMEs was positively and significantly impacted by business scale. The performance of MSMEs improves with increasing firm scale. The performance of MSMEs is also positively and significantly impacted by financing; the easier it is for MSMEs to get financing, the better their performance will be. Additionally, the performance of MSMEs is positively and significantly impacted by bank partnerships; the stronger the relationship between MSMEs and banks, the higher the performance of MSMEs. The performance of MSME's is also significantly impacted by bank financial ties, funding, and business scale. It is advised that MSMEs in Bengkong Subdistrict continue to grow their businesses, broaden their access to funding, and cultivate positive banking connections in light of the study's findings. To increase corporate performance and competitiveness, MSMEs also require extensive support and help from local governments and affiliated organisations.